Regulatory elements involved in the bidirectional activity of an immunoglobulin promoter. - Doyen, N (1989)
We show that the promoter from the mouse VH441 heavy-chain immunoglobulin gene, when present on plasmids transiently introduced into myeloma cells, promotes transcription bidirectionally, due to the presence on both strands of TATA-like sequences bracketing the highly conserved decanucleotide element. The two divergent promoters compete for the transcriptional machinery, their relative strength ultimately reflecting the likeness of the two TATA boxes to the consensus sequence. Moreover, their relative activity is also strongly influenced by certain point mutations within the distally located heavy-chain enhancer. The bearing of these results on current concepts of promoter function is discussed.